Promising novel biomarkers in cardiovascular diseases - Sipos, Brigitte; Jirak, Peter; Paar, Vera; Rezar, Richard; Mirna, Moritz; Kopp, Kristen; Hoppe, Uta C.; Berezin, A. E.; Lichtenauer, Michael; Березін, Олександр Євгенійович (MDPI Multidisciplinary Digital Publishing Institute, 2021)
Cardiovascular diseases remain the most common causes of death globally, according to the World Health Organization. In recent years, a great number of biomarkers have been investigated, whereas only some have gained value in the diagnosis, prognosis, and risk stratification of different cardiovascular illnesses. As numerous studies have investigated the diagnostic yield of novel biomarkers in various disease entities every year, this review aims to provide an overview of the current status of four promising representatives. In particular, this manuscript refers to soluble suppression of tumorigenicity 2 (sST2), heart-type fatty acid binding protein (H-FABP), growth differentiation factor (GDF-15) and soluble urokinase-type plasminogen activator receptor (suPAR). These markers are of special interest as they are thought to provide an accurate estimate of cardiovascular risk in certain patient populations, especially those with pre-existing diseases, such as obesity or diabetes mellitus. We sought to give an overview of their function, individual diagnostic and predictive value and determination in the laboratory. A review of the literature regarding the aforementioned cardiovascular biomarkers yielded manifold results with respect to their individual diagnostic and prognostic value. Yet, the clinical relevance of these findings remains unclear, warranting further studies to identify their optimal use in clinical routine.
Keywords: cardiovascular disease; biomarkers; sST2; H-FABP; GDF-15; suPAR